Is common agricultural policy competent to steer EU agriculture in turbulent times? Evidence from the European dairy sector - Artiom Volkov; Mangirdas Morkūnas; Maria Crescimanno (Agricultural and Food Economics)
Abstract The present study introduces a sophisticated index of the susceptibility of the dairy sectors of various EU countries to external turbulence. The index, created using the technique for order of preference by similarity to ideal solution multi-criteria decision-analysis using monthly data from January 2015 to July 2023, allows us to comprehensively evaluate the susceptibility of the European dairy sector to external shocks and to identify particular regions or countries that require additional support from regulatory bodies even before the negative external shocks affects the respective regions. Regulators can thus act proactively to increase the resilience of the dairy sector to avoid serious negative effects. The results show that under the current regulatory regime the most susceptible dairy sectors in the European Union are in Hungary and the Baltic States, while the most resilient appear to be Cyprus, Malta and Greece dairy sectors. The difference amounts more than 100% in index value. There is a need for urgent measures to assist the dairy sectors in the most susceptible countries as processes eroding their sustainable development of a dairy sectors in these countries (e.g. selling cows for meat) have already begun. The structural breaks in the development of the index are identified and analysed.